STUDY OF BENZENE VAPOR ADSORPTION BY LOGON BENTONITE AND ITS ORGANIC MODIFICATIONS - No‘monov M.A.; Abdikamalova A.B.; Mirsalimova S.R.; Eshmetov I.D. (Innovate Conferences, 2025)
Bentonites are naturally occurring hydrated aluminosilicate minerals widely used due to their high ion-exchange capacity and large specific surface area. As a result, bentonite is commonly applied in adsorption processes across various environmental and industrial domains [1]. The adsorption properties of bentonite are effectively utilized in applications such as environmental remediation, water purification, and the separation of various chemical substances. One effective approach to enhancing the adsorption capacity of bentonite is through its modification. During the modification process, both the structure and surface characteristics of bentonite are altered, which significantly improves its adsorptive performance.